Bi-objective optimal design of a damage-tolerant multifunctional battery system. (5th September 2016) - Nguyen, Trung N.; Siegmund, Thomas; Tsutsui, Waterloo; Liao, Hangjie; Chen, Wayne
Abstract: In current electric vehicles (EVs), battery systems only serve the role of electrical energy storage. Heavy protecting structures surround the batteries. To enhance the overall performance of EVs one desires multifunctional battery systems with structural and energy storage functionalities. Our research centers on the design methodology to enable such multifunctional material systems. An architectured multifunctional battery-structure material system, namely the Cellular Battery Assembly (CBA), is introduced. The CBA is composed of cylindrical battery cells surrounded by hollow tubes. The CBA inherits features of the energy absorbing characteristics of periodic cellular materials while maintaining an electrical energy storage. The energy absorbing mechanism is activated when intentional collapse of hollow tubes dissipates energy and protects battery units from high compressive stress. Depending on loading conditions to be applied, the multi-functionalities of CBA can be optimized by morphological or dimensional control of the building blocks through a multi-objective optimization process. The present study focuses on a multi-objective optimization design process to achieve optimal configurations in specific applications where energy storage and energy absorption are objective functions to be maximized simultaneously. Results show that CBA can possess energy absorption performance that compares well to other energy absorbing materials while a desirable energy storage capability is maintained. Graphical abstract: Highlights: A multifunctional material system combines metal tubes and batteries in a periodic assembly to provide energy absorption and energy storage. Optimization of the material system employs problem intrinsic parameters without resorting to external weight or performance functions. Optimal material architectures can simultaneously achieve high energy storage, and substantive energy absorption.